A expansão dos interesses mercantis do Recife (PE – Brasil) nos “sertões de fora”: Uma análise a partir da trajetória do coronel João de Barros Braga na capitania do Siará Grande: La expansión de los intereses mercantiles de Recife (PE – Brasil) em los “Sertones de Fuera”: un análisis a partir de la trayetoria del Coronel João de Barros Braga en la Capitanía de Siará Grande (Revista de História da UEG (REVHIST), 2020)
The expansion of the commercial interests of Recife (PE - Brazil) in the “sertões de fora”: An analysis from the trajectory of Colonel João de Barros Braga in the captaincy of Siará GrandeAbstract: The end of the 17th century and the beginning of the 18th century comprised a period of great transformations in Portuguese America that, in Pernambuco and regions under its influence, was marked by wars related to the expansion of livestock farming and by the strong regional antagonism between segments associated with the interests of the traditional sugar elite of Pernambuco and the emerging mercantile elite of Recife. This article [1] has as main objective to analyze the process of conquest of the hinterlands by the advance of cattle raising taking as reference the conflict between the sugar elite and the mercantile elite of Pernambuco. With the objective of perceiving the advance of the interests of the mercantile elite in the process of expanding livestock in the captaincy of Siará Grande, the discussion takes as main reference for analysis the networks of relations established in the middle of this process by Colonel João de Barros Braga, a prominent subject in the captaincy of Siará Grande amidst the conjuncture of wars of conquest.Keywords: Elite Mercantil. Livestock. Captaincy of Siará Grande.